Farm-SAFE v3 - Comparing the financial benefits and costs of arable, forest, and agroforestry systems - Graves, Anil; Burgess, Paul J.; Wiltshire, Catherine; Giannitsopoulos, Michail; Herzog, Felix; Palma, João H. N. (Cranfield University, 2024)
Agroforestry systems integrate trees with livestock and/or arable crops on the same parcel of land. Compared to monoculture arable or grass systems, agroforestry systems can enhance soil conservation, carbon sequestration, species and habitat diversity, and provide additional sources of farm income. Farm-SAFE (Financial and Resource use Model for Simulating AgroForestry in Europe) is a spreadsheet-based bio-economic model which has been developed in Microsoft® Excel® to compare the financial benefits and costs of crop-only, tree-only, and agroforestry system over tree rotations of up to 60 years (Graves et al., 2024a). The results are presented in both graphical and tabular form in terms of a net present value and equivalent annual values. A description and user guide is also available (Graves et al., 2024b). Farm-SAFE requires input of tree and crop yields. One way to obtain crop and tree yields in tree-only, agroforestry, and crop-only systems is to use the Yield-SAFE model. Yield-SAFE is a spreadsheet-based biophysical model which has been developed to enable the prediction of the relationship between tree and crop yields over the rotation of the tree component. A copy of the Yield-SAFE model, together with a full description and user guide, is available here. The original Farm-SAFE model was developed with funding from the European Union through the Silvoarable Agroforestry For Europe project (contract number QLK5-CT-2001-00560). The process of creating a default publicly available version of the model has been enabled through the BioForce project funded by the UK Department for Energy Security and Net Zero. Graves, A.R., Burgess, P.J., Wiltshire, C., Giannitsopoulos, M., Herzog, F., Palma, J.H.N. (2024a). Farm-SAFE v3 model in Excel. Cranfield, Bedfordshire, UK: Cranfield University. Graves, A.R., Burgess, P.J., Wiltshire, C., Giannitsopoulos, M., Herzog, F., Palma, J.H.N. (2024b). Description and User Guide for Farm-SAFE v3. January 2024. Cranfield, Bedfordshire, UK: Cranfield University. 42 pp.
Keywords: Agroforestry'; 'Farm-SAFE'; 'Farm economics'; 'Profit'; 'crop yields'; 'silvoarable'; 'silvopasture'